2010
DOI: 10.1103/physrevb.81.064102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vacancy defects in a thin film perovskite oxide

Abstract: Vacancy defects in thin film laser ablated SrTiO 3 on SrTiO 3 were identified using variable energy positron annihilation lifetime measurements. Strontium vacancy related defects were the dominant positron traps and, apart from in the top ~ 50 nm, were found to be uniformly distributed. The surface layer showed an increase in annihilation from larger open-volume defects, large vacancy clusters or nanovoids.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 31 publications
5
39
0
Order By: Relevance
“…3). This result supports the suggestion that relatively small amounts of cation non-stoichiometry, which were demonstrated to occur even in nominally stoichiometric PLDgrown samples, 20,21 can lead to the appearance of polar nanoregions and relaxor-like ferroelectricity, as reported by Jang et al 13 In summary, Sr/Ti non-stoichiometry in homoepitaxial SrTiO 3 films leads to the appearance of first-order peaks in Raman spectra, which are symmetry-forbidden in paraelectric SrTiO 3 . Strontium-deficient samples, in particular, exhibit a temperature evolution of Raman spectra consistent with a ferroelectric phase transition with the transition temperature ∼350 K. Similar spectra have been recorded from nominally stoichiometric PLD samples proven to be ferroelectric.…”
supporting
confidence: 78%
“…3). This result supports the suggestion that relatively small amounts of cation non-stoichiometry, which were demonstrated to occur even in nominally stoichiometric PLDgrown samples, 20,21 can lead to the appearance of polar nanoregions and relaxor-like ferroelectricity, as reported by Jang et al 13 In summary, Sr/Ti non-stoichiometry in homoepitaxial SrTiO 3 films leads to the appearance of first-order peaks in Raman spectra, which are symmetry-forbidden in paraelectric SrTiO 3 . Strontium-deficient samples, in particular, exhibit a temperature evolution of Raman spectra consistent with a ferroelectric phase transition with the transition temperature ∼350 K. Similar spectra have been recorded from nominally stoichiometric PLD samples proven to be ferroelectric.…”
supporting
confidence: 78%
“…1), and the behavior of c with F (Figs. 2 and 4), it is expected that the film grown with optimal fluence, 1.50 J cm The results obtained from the Ti-deficient films were found to be quite different from the systematic trends observed for 28 A recent study of two La-doped MBE-grown SrTiO 3 thin films also observed positron trapping to a defect lifetime component in the range ∼370-420 ps in the near-surface ( 50 nm) regions. 32 Further, a lifetime component at 430(10) ps has also been reported from a VE-PALS measurement of a strongly oxygen depleted Nb-doped SrTiO 3 substrate behind an ∼30 nm MBE-grown BaTiO 3 layer.…”
Section: Resultsmentioning
confidence: 80%
“…37 The DFT calculated lifetime for a Schottky defect consisting of both V Ti and V Sr with three nearest neighbor oxygen vacancies has been given as 316 ps. 28 Vacancy clustering has also been studied in silicon, wherein the positron lifetime systematically increases with the number of vacancies, a value of 355 ps has been reported for a five vacancy cluster, 38 and lifetimes in the range 420-430 ps have been associated with vacancy clusters containing between 10 and 14 vacancies. 39 Recently, atomic-resolution scanning tunneling microscopy images of processed SrTiO 3 (001) surfaces have shown Ti 4 O 3 vacancy cluster defects in the surface Ti terminated surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations